Research progress of cytokine mediated pluripotent stem cells into salivary gland differentiation - CHENG Taiqi, YAN Xing (Xin yixue)
Currently， tumor and radiotherapy can result in physiological and functional damage to the salivary glands， significantly impacting the physiological and psychological well-being of patients. The repair of salivary gland injuries remains a challenging aspect of clinical treatment. Tissue regeneration engineering through cytokine-mediated stem cell directed differentiation offers a novel therapeutic approach for addressing salivary gland injuries. Embryonic stem cells （ESC） and induced pluripotent stem cells （iPSC）， with their potential for multidirectional differentiation and self-renewal， play a crucial role in regenerating and repairing salivary gland tissue. Building upon studies on classical tridermal differentiation of ESC/iPSC mediated by cytokines， this paper provides an extensive review on the research progress and future prospects of utilizing cytokine-mediated stem cell differentiation for salivary gland regeneration.